Prospective evaluation of a closed-incision negative pressure wound therapy system in kidney transplantation and its association with wound complications - Lam, Susanna; Huynh, Annie; Ying, Tracey; Sandroussi, Charbel; Gracey, David; Pleass, Henry C.; Chadban, Steve; Laurence, Jerome M. (Frontiers in Nephrology, 2024)
Introduction: Wound complications can cause considerable morbidity in kidney transplantation. Closed incision Negative Pressure Wound Therapy (ciNPWT) systems have been efficacious in reducing wound complications across surgical specialties. The aim of this study was to evaluate the use of the ciNPWT, Prevena™, in kidney transplant recipients and determine any association with wound complications. Material and Methods: A single center, prospective observational cohort study was performed in 2018. Thirty consecutive kidney transplant recipients deemed high risk for wound complications, received the ciNPWT, and results were compared to a historical cohort of subjects who received conventional dressings. Analysis for obese recipients and propensity score matching was performed. Results: There were 127 subjects in total included in the analysis, thirty received a ciNPWT dressing and were compared with 97 subjects in the non study historical control group who had a conventional dressing. Overall wound complications rates were 21.3% (27/127). There was no reduction in the rate of wound complications with the ciNPWT when compared to conventional dressings (23.3%; 7/30 vs 20.6%; 20/97, respectively, p=.75). In the obese (BMI ≥30kg/m2) subset there was no significant reduction in wound complications (31.1%; 5/16 vs 36.8%; 7/19, respectively, p =.73). Propensity score matching yielded 26 matched pairs with equivalent rates of wound complications (23.1%; 6/26). Conclusion: This is the first reported cohort study evaluating the use of ciNPWT in kidney transplantation, and whilst the ciNPWT is safe and well tolerated, it is not associated with a statistically significant reduction in wound complications when compared to a conventional dressing. The lessons learned from this study will be used to inform future studies associated with the ciNPWT in kidney transplantation.